Thermal ocular injury associated with retinal necrosis and vitreous inflammation: a case report - Ruiping Gu; Ruiping Gu; Ruiping Gu; Ruiping Gu; Yue Guo; Yue Guo; Yue Guo; Yue Guo; Yue Guo; Boya Lei; Boya Lei; Boya Lei; et al. (Frontiers in Medicine, 2025)
BackgroundA case of thermal ocular injury associated with retinal necrosis and vitreous inflammation is reported.Case presentationA 53-year-old man’s right eye was hit by a heated screw, which embedded directly into the nasal orbit. Two weeks after the foreign body was removed, serious vitreous inflammation and a large yellow–white lesion on the nasal peripheral retina, which resembled a subretinal abscess, were observed. Endophthalmitis could not be ruled out and vitrectomy was performed. During vitrectomy, we identified the yellow–white lesion as retinal necrosis and edema, with localized retinal detachment within the lesion. After surgery, there was significant macular atrophy with poor vision.ConclusionThermal retinal burns must be differentiated from infectious endophthalmitis to ensure timely anti-inflammatory treatment.